DETERMINANT OF FINANCIAL DISTRESS IN FOOD AND BEVERAGE COMPANIES - Naura Bilqis Tasyakurina; Anik Yuliati (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
This study aims to analyze and empirically test the effect of operating capacity, operating cash flow, and sales growth on financial distress in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. In particular, this study wants to determine the effect of each variable partially or simultaneously on the company's financial distress condition. The approach used in this research is quantitative with descriptive methods. The sample was selected using purposive sampling technique, so that 60 financial reports were obtained from a total of 251 reports in the population. Thus, the sample data to be used in this study amounted to 60 which were calculated based on the total observation period consisting of 20 food and beverage companies for the 2021-2023 period. The data used is secondary data which is analyzed using the panel data regression method with the help of Eviews 12 software. The results showed that operating capacity and sales growth have no significant effect on financial distress. However, operating cash flow has a negative and significant effect on financial distress. Simultaneously, the three independent variables, namely operating capacity, operating cash flow, and sales growth, have an effect on financial distress.